Pedagogical environmental education university, a contribution to sustainable human development with social responsibility - Mindiola González, Rubelys (2017)
The present doctoral educational documentary research, not experimental, sought from its general objective to develop a strategy for the environmental pedagogical training of university teachers, thus achieving, resize the role of universities in the awareness and actions that impact so positive, the increasing deterioration of the planet, product of global warming, and its consequent natural disasters. This research had as scenarios the different houses of university studies of Cabimas, with a total of 45 professors. Applying theoretical, logical, inductive deductive, empirical methods and analysis. Among the information collection techniques used, the interview and observation stand out, as well as the bibliographic file, underlined in: libraries, newspaper archives, internet, constitution, laws, regulations, norms, decrees, research works, thesis. It is concluded that in the analysis carried out they show evident theoretical weaknesses in the process of the permanent formation of the university professors, from the environmental pedagogical perspective, by not sufficiently systematizing the logic in their conception. In this sense, it reveals the need to conceive a theoretical construct that is an expression of an environmental pedagogical preparation as a quality that favors integration in this process. Therefore, it is recommended to design and implement a training program, which makes it possible to strengthen university education for the systemic and transdisciplinary approach to environmental issues.